The experience of social isolation in patients receiving peritoneal dialysis: a qualitative study - Keke Diao; Jiajia Wang; Yijia Huang; Yanjun Zhang; Dingshuo Guo; Luke Zhang; Yan Shan (BMC Psychology)
Abstract Background Social isolation(SI), as a negative psychological state, can aggravate sleep disturbances and deterioration of renal function, seriously jeopardizing physical health, which is particularly prominent in peritoneal dialysis(PD) patients. However, most of the current research in this field is quantitative, and there are few qualitative studies on SI in PD patients. Understanding patients’ psychological experience of SI is essential for the targeted design of intervention programs. Therefore, the aim of this study is to investigate the experience of SI among PD patients. Methods 12 peritoneal dialysis patients who were hospitalized in a tertiary hospital in Zhengzhou City, Henan Province, were selected for the study using purposive sampling. Semi-structured in-depth interviews were conducted to collect data, and content analysis methods were used to analyze the data. Results A total of 4 themes and 16 sub-themes were analyzed and extracted from this study, namely: (1) Objective manifestations of social isolation(Work isolation, Entertainment isolation, International isolation, Self isolation); (2) Subjective emotional feelings of social isolation. (Low self-esteem and sensitivity, Fear and concern, Solitude and loneliness, Dissembling and deception); (3) Multiple obstacles exacerbate the plight of social isolation(Shackles of over protection, Lack of self-worth, Agony of public misunderstanding, Burden of treatment expenditure, Limitation of treatment conditions); (4) Patients still crave multiple forms of social support(Appreciate Family support, Value Peer Support, Call for social support). Conclusion This study provides insight into the experience of SI in PD patients and the reasons for it. SI in PD patients can manifest as Objective manifestations and Subjective emotional feelings that create significant psychological problems. The degree of SI is aggravated by multiple factors such as lack of self-worth and lack of public awareness. In the future, it is necessary to provide support to improve the SI problem through the collaboration of multiple fields such as family, peers and society.